IMPLEMENTASI STRATEGI PEMBELAJARAN BERBASIS PROYEK DALAM PEMBELAJARAN PAI - Rian Dwi Saputra; Rezki Kaela Febriyani; Najwa Azwina; Bakti Fatwa Anbiya (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
Learning continues to experience development and variation, including in Islamic Religious Education (PAI), so that innovative strategies are needed that suit the needs of students. One of the strategies that can be implemented is project-based learning. This study aims to systematically analyze relevant literature regarding the implementation of the strategy in Islamic Education learning. The method used is systematic literature review, which aims to summarize research results from literature sources related to this topic. Data were collected through information searches from scientific journal articles that have been determined by the criteria. The data obtained were organized in the form of interrelated narratives to provide a comprehensive picture of the development of research in this field. The results showed that project-based learning in PAI involves structured stages, namely planning, implementation and monitoring, and evaluation. The implementation of this strategy is proven to have a positive and significant impact on student learning outcomes, thus supporting the effectiveness of PAI learning. This study serves as an important guide for educators, policy makers, and researchers in organizing more meaningful learning.